Diagnóstico de lesões incipientes de mancha branca por análise de imagens de laser speckle - Silva, João Vagner Pereira da (2016)
Dental caries is considered a complex, multifactorial disease that determines the localized destruction of mineralized tissues. It is also influenced by the time factor and is described as a process dependent on specific interactions between microorganisms, carbohydrates and a susceptible tooth surface The aim of this study was to develop a methodology of identification and quantification dental decay noninvasively, with low-cost and real-time execution, by using laser speckle imaging analysis. We used 45 samples of bovine incisors divided into 3 groups where we induced injured areas, each sample had two distinct areas, healthy half and half with artificially induced decay. The samples were illuminated by light laser and photographed by digital camera it was possible to observe the formation of optical speckle caused by interference between the various scattered light beams. The injury was evidenced by segmenting the image through a proprietary software.